القياس الاقتصادي لأثر التحرير المالي لمعدلات الفائدة على حجم الادخار في الاقتصاد الجزائري للفترة (1990ـ2013) - الزهر, د/ بن بريكة; سلامي, / أحمد (Sciences humaines; Vol. 42 (2015): SCIENCES HUMAINES (Novembre ), 2016)
يهدف هذا البحث إلى تحليل العلاقة طويلة الأجل بين التحرير المالي لمعدلات الفائدة وحجم الادخار         في الجزائر خلال الفترة (1990ـ2013). النتائج تكشف عن عدم وجود دلائل لعلاقة توازنية في المدى الطويل بين المتغيرين، وبالتالي عدم فاعلية سياسة تحرير سعر الفائدة التي انتهجتها الحكومة في جذب المدخرات، الأمر الذي يؤكد على أن هناك عواملا اجتماعية وثقافية ودينية تجعل من سعر الفائدة عاملا غير مؤثر على الادخار،  الأمر الذي لا يمكن الاعتماد عليه     في رسم السياسات المتعلقة بالادخار   في الجزائر. وهذا يقود إلى ضرورة الاتجاه نحو اعتماد المعاملات المالية الخالية من سعر الفائدة. This research aims to long-term relationship analysis between financial liberalization of interest rates and the size of the savings in Algeria during the period (1990-2013). The results reveal a lack of evidence of the relationship of equilibrium in the long run between the two variables, and therefore the ineffectiveness of Liberalization of interest rate policy pursued by the government in attracting savings, which confirms that there are social, cultural and religious factors makes interest rate  is Factor is ineffect on savings, Thereby can not be relied upon in policies related to saving in Algeria . This leads to the need to move towards the adoption of  financial transactions absent from interest rate.